Psychological Defenses of Students in Confronting the Stressors of Military Actions - Plokhikh , Viktor; Bilous , Ruslana (Insight: the psychological dimensions of society, 2025)
The study aims to determine the relationship between the implementation of psychological defenses, acceptable for current adaptation, and the level of stressful neuropsychiatric tension among students (civilians) under the influence of stressors of military actions. Methods. 109 students of Bachelor and Master degree levels of higher education (aged 18 to 55) were participants of this research. The following methodologies were used in this research: the methodology “Life style index” (H. Kellerman, R. Plutchik, H.R. Conte); Freiburg Personality Inventory (FPI, form “В”); the methodology of C. Spielberger in order to determine the level of trait and situational anxiety; the scale of psychological stress PSM-25; the methodology for determining the level of stress by V. Shcherbatuh. Results. One-third of a total group of subjects (32.11 %) have significantly pronounced tension states of anxiety and stress. Among three groups of subjects identified via cluster analyses, there are significant differences in the following indicators: the level of stress (χ2 = 10.423; df = 2; p = .005); situational anxiety (χ2 = 14.461; df = 2; p = .001); trait anxiety (χ2 = 9.318; df = 2; p = .009). Using psychological defenses significantly changes with the increase of stressful neuropsychiatric tension in the groups: projection (χ2 = 77.289; df = 2; p < .001), rationalization (χ2 = 63.652; df = 2; p < .001), and compensation (χ2 = 12.367; df = 2; p = .002). There are two factors identified via exploratory factor analysis that explain 41.87 % of accumulated variance: Factor 1 (combining all parameters characterizing the presence of stressful neuropsychiatric tension and parameters related to the subjects’ loss of stress resistance resources and opportunities for adequate resistance to stressful influences) and Factor 2 (combining the vast majority of psychological defenses). Discussion and Conclusions. Psychological defenses of students (civilians) from the stressors of military actions are conceptually defined as a method of adaptive response to current threats, which is usually characterized by a general acceptance of reality, partial content inadequacy of response to significant impacts of threatening circumstances in order to eliminate or significantly weaken the impact of emotionally difficult, undesirable for perception, psychologically traumatic information. Among the psychological defenses of students in confronting the stressors of military actions, projection, rationalization, and compensation were the most expressive and significant. With excessive expressiveness of tense states and difficulty in organizing mental actions, compensatory resources of rationalization and compensation, as well as other psychological defenses, become insufficient for the necessary reduction of neuropsychiatric tension. As distress develops, the activation of destructive projection also increases. 25; the methodology for determining the level of